Analysis of Musyawarah Rencana Pembangunan (MUSRENBANG) as The Realization of a Participatory Development Planning System in Indonesia - Rizki Nanda Saputri; Noviana Simbolon (Mahadi: Indonesia Journal of Law, 2023)
Indonesia has introduced a development planning system in which communities and stakeholders are directly involved in development agencies. This system is known as Musyawarah Rencana Pembangunan or MUSRENBANG. It reflects the national form of Indonesia as the democratic state; thus, all stakeholders are directly involved in the development planning process at village, sub-district, district, city and state level. Indonesia has introduced consultation on development planning as a form of participatory planning and has become a mandatory agenda item for all local governments. Participation from various stakeholders, including the community, is expected, but obstacles still face. On the one hand, the plans that are implemented tend to prioritize the physical needs of the area over improving the economy of the community. While many comments have been made regarding the implementation of MUSRENBANG, maximum community involvement can increase public confidence in local government.